Effect of distance from the Cagayan de Oro controlled dumpsite on the groundwater quality of shallow dug wells. - Yanilla-Leocadio, RJ Krista Raye
The study ventured into comparing the selected physical and chemical parameters of water in the areas near and far from the Cagayan de Oro controlled dump site. Specifically, it compared the physical parameters of water as regards color and turbidity, as well as the chemical parameters of water as regards pH, total dissolved solids (TDS), sulfate, chloride and nitrate. Findings showed that the proportion of sampled wells that yielded poor in color was not significantly poor in areas far from the dump site. On the chemical parameters of water, the proportion of sampled wells that yielded poor in total dissolved solids (TDS) was significantly higher in the areas far from the dump site compared to the areas near the dump site. All the rest of the chemical parameters like the pH, sulfate, chloride and nitrate of the groundwater in wells were within the permissible limits prescribed by the Philippine National Standards for Drinking Water (PNSDW) of 2007. In recapitulation, the q2uality of water in the shallow dug wells of Cagayan de Oro City posts and will post hazard to the environment and the health of the consumers. With these preceding assessments of groundwater quality understudied, it is strongly recommended that further study, with an appropriate plan and design, on the hydro-geological formation of the Cagayan de Oro controlled dump site be conducted, and eventually race the flow of leachate, that the provisions of the Ecological Solid Waste Management Act (RA 9003) should be strictly implemented so that operation of the controlled dump site can be made comprehensively, and that well-fashioned linings of wells should be built to assure durable, stable, and uninterrupted prevention from contaminants. Only then the consumers' health, in terms of drinking water and other domestic purposes, are very well safeguarded
Thesis (MS Public Health, Environmental Health)--University of the Philippines Manila, 2013
Keywords: Water quality